The Holy Woman - Shahraz, Qaisra (Islamabad Alhamra, 2002)
A lean, lyrical meditation on tradition and independence, sensuality and sacrifice, set against the mortal background of modern day Pakistan, Shahraz's debut beguiles throughout." -The Times"Stunning debut novel. An intricate study of love, family, politics and sacrifice." - Eastern Eye'Qaisra Shahraz has a real story-telling gift ...' - Sue Gee'...very moving tale of love, passion and Islamic traditions...difficult to put down...compelling read' - BBC National Asian Network'...a remarkable new novel' - Asian News'A dramatic story of family intrigue, religious passions and riproaring romance' - Michele Roberts'Intriguing tale of love, envy and jealousy ... Compulsive reading... Must not be missed ... A definite hit ...' - Asian Times
Keywords: Muslim Families -- Pakistan--Karachi -- Domestic Fiction